TINJAUAN YURIDIS PENGELOLAAN ROYALTI HAK CIPTA LAGU DAN/ATAU MUSIK MENURUT PERATURAN PERUNDANG-UNDANGAN YANG BERLAKU DI INDONESIA - Iswantono, Tanu; Rosando, Abraham Ferry (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2022)
Songs and musics are a creation of human being that being protected by the law. This protection is made for giving welfare for certain people that created the songs or musics, in economics or non-economics ways. For those, Indonesian government make some rules, from the very beginning like Undang-Undang Dasar Negara Kesatuan Republik Indonesia 1945 until the specific ones like Peraturan Pemerintah No.56. These rules also supported by many norms such as Peraturan Kementrian Hukum dan HAM, and the other positive law which exist in Indonesia. The purpose of this efforts is to decrease uncertainty law about songs and musics sharing profit in Indonesia